Appraisal of Alum Sludge Waste for Low-Carbon, Calcium Aluminate Cement Production - Pavia, Sara (ISBN: 978-989-54499-3-4, 2023)
Calcium aluminate cement (CAC) is the most used non-Portland cement, known for its rapid hardening and high thermal resistance. The difficulty in obtaining raw materials, mainly bauxite, has resulted in the current high price of CAC. Alum sludge waste (AS) is a flocculating precipitate, high in aluminium, produced during the water purification process in drinking water treatment plants. The potential of using locally available AS, as an aluminium source, to produce CAC was investigated. This serves a dual purpose: to reduce bauxite dependence and to recycle waste. In addition, the CAC produced with AS waste would have embodied lower carbon than existing conventional cements. Cements were produced by calcining AS and lime blends, at 1:1 and 1:3 ratios, at 1100, 1200 and 1300°C. The composition and properties of the resultant cements and their hydrates were studied with mechanical tests, X-ray diffraction (XRD) and scanning electron microscopy (SEM). The main reactive phases of the CACs were calcium aluminates such as C3A and C12A7. Higher calcination temperatures result in reaction products of higher Ca/Al ratios. Hexagonal interlocking C-A-H hydrates were observed in the CAC pastes. The CAC prepared with a 1:3 (AS:lime) ratio sintered at 1300°C displayed the best performance, whereas high aluminium contents and low calcination temperatures caused flash setting and severe expansion.
Proceedings of the 2nd Int. Conf. Construction, Energy, Environment and Sustainability - CEES 2023
Keywords: Cementing ability; Waste reactivity; Low-carbon cement; Calcium aluminate cement (CAC); Alum sludge waste (AS); Nanoscience & Materials; Smart & Sustainable Planet